Delving into Critical Incident Experiences of EFL Teachers: A Lesson Study Reflection - Yuli Ari Sandy; Paulus Kuswandono (English Education:Journal of English Teaching and Research, 2026)
This qualitative research explored Critical Incident (CI) experiences of English as a Foreign Language (EFL) teachers through the frame of Lesson Study (LS). Five EFL local teachers at SMPN 1 Nguter participated in this research. The purpose of this study was to explore the impacts of Critical Incident (CI) experiences on the professional development of English as a Foreign Language (EFL) teachers and to examine how these experiences influenced their teaching practices at SMPN 1 Nguter through the framework of Lesson Study. The study also aimed to understand how reflective practices within lesson study activities could contribute to the development of adaptive, student-centred, and culturally responsive teaching strategies. Data were collected using interviews, observation, guided reflection, and document analysis. A narrative inquiry research design was applied. The data were analyzed through triangulation and coding (open-, axial-, and selective coding). The result indicated that the impact of CI experiences on TPD includes emotional resilience, pedagogical improvement, professional learning community, and lifelong learning. These experiences improved teaching practice by supporting adaptive teaching strategies, particularly in rural contexts. Reflective CI analysis can promote more student-centered and culturally responsive teaching. These findings emphasizes the importance of structured reflection within collaborative frameworks, such as lesson study (LS), to promote continuous professional development among EFL teachers in similar educational setting worldwide.  Further research is needed to explore the long-term impact of reflective practice on teaching effectiveness and student outcomes.